Pengaruh Kualitas Pelayanan terhadap Kepuasan Jamaah pada PT. Marifat Wisata Mandiri di Kabupaten Lebak - Zakiyya Tunnufus; Eris Harismasakti; Dinda Rahmawati (E-Journal Studia Manajemen, 2012)
This study aims to find empirically services quality on customers satisfaction PT Ma’rifat Wisata Mandiri, Lebak. The research method used is descriptive quantitative with survey method. This study uses probability sampling method with simple random sampling. The sample consisted of 105 consumers. The results showed that there are significant services quality on customers satisfaction.